Resubmission of interim payment application no. 022 (Rev.01) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding resubmission of interim payment application no. 022 (Rev.01) of BRAC University new campus project.